2021
DOI: 10.1002/er.6557
|View full text |Cite
|
Sign up to set email alerts
|

Simple synthesis and electrochemical performance of NaVSi 2 O 6 as a new sodium‐ion cathode material

Abstract: Summary Developing new sodium‐ion battery (SIB) cathode materials with low cost and high capacity remains a challenge. Here, NaVSi2O6 was successfully synthesized by a simple sol‐gel method for the first time. This material was used as a new SIB cathode material. At a current density of 20 mA g−1, the first discharge specific capacity is 80 mA h g−1, which exhibits a higher capacity. The mechanism of the cycle stability of NaVSi2O6 was elucidated by the theoretical calculations. The volume and formation energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For the first time, Wei et al [69] synthesized NaVSi 2 O 6 cathode material by the simple sol-gel method. Combined with DFT, they calculated the formation energy changes of Na + insertion with different contents and determined the structural changes of the material during charging and discharging by using the volume changes.…”
Section: Analysis Of Electronic Structurementioning
confidence: 99%
“…For the first time, Wei et al [69] synthesized NaVSi 2 O 6 cathode material by the simple sol-gel method. Combined with DFT, they calculated the formation energy changes of Na + insertion with different contents and determined the structural changes of the material during charging and discharging by using the volume changes.…”
Section: Analysis Of Electronic Structurementioning
confidence: 99%
“…Interest in AVSi 2 O 6 (A = Li and Na) materials as cathodes for the application of rechargeable batteries has emerged in recent years due to the existence of variable oxidation states of vanadium, leading to redox reactions [34][35][36]. Li 2 VSi 2 O 6 was reported to be a potential cathode material for use in Li-ion batteries [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Two different high capacities of 85 mAhg -1 and 181 mAhg -1 were measured at 30 • C and 60 • C, respectively, due to the introduction of additional 0.42 Li + ions arising from redox reactions (V 3+ /V 4+ and V 2+ /V 3+ ) [34]. Very recently, a sol-gel method was used to prepare a high-capacity NaVSi 2 O 6 cathode material yielding a specific capacity of 80 mAhg -1 [36]. Density functional theory simulation was used to examine the stability of Na insertion into NaVSi 2 O 6 , and it was concluded that poor cycle stability is directly related to the significant volume change [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation